منهج فقهاء الشافعية في عرض الفروق الفقهية: Methodology in Presenting of al-Furūq al-Fiqhiyyah by Fukahā in Shafi'i School - Akhmad Hanafi Dain Yunta (البصيرة: مجلة الدراسات الإسلامية, 2020)
Several scholars of fiqh of the Shafi'i School in presenting fiqh issues used the method of deciphering aspects of the differences between legal issues that had a similar picture but had differences in terms of the law, which was later known as al-furuq al-fiqhiyyah. Since the beginning of the writing of al-furuq al-fiqhiyyah, there had been some literature that discussed it specifically or which specializes it in a sub-discussion. However, the researcher found in this literature that there are significant differences in the method of presentation among the authors. Because of that, it is considered important to formulate a separate method of approach as a general standard to recognize the character of scientific works on al-furuq al-fiqhiyyah. In this study, the researcher used the inductive istinbat method of approach, by inducing possible and representative works of literature related to al-furuq al-fiqhiyyah in the Shafi'i School. This study found that the Fuqaha of Shafi'i school used four ways in presenting the discussion of al-furuq al-fiqhiyyah, namely: Describing the discussion of al-furuq al-fiqhiyyah in one separate literature, describing it in the literature related to al-farq (differences), and al-istisna' (exception), describing it in the literature that specifically discusses a particular problem or issues, and describes it in the literature that simply inserted a discussion of al-furuq al-fiqhiyyah as a complement.